Programmable diffractive optical elements for extending the depth of focus in ophthalmic optics (2015)
The depth of focus (DOF) defines the axial range of high lateral resolution in the image space for object position. Optical devices with a traditional lens system typically have a limited DOF. However, there are applications such as in ophthalmology, which require a large DOF in comparison to a traditional optical system, this is commonly known as extended DOF (EDOF). In this paper we explore Programmable Diffractive Optical Elements (PDOEs), with EDOF, as an alternative solution to visual impairments, especially presbyopia. These DOEs were written onto a reflective liquid cystal on silicon (LCoS) spatial light modulator (SLM). Several designs of the elements are analyzed: the Forward Logarithmic Axicon (FLAX), the Axilens (AXL), the Light sword Optical Element (LSOE), the Peacock Eye Optical Element (PE) and Double Peacock Eye Optical Element (DPE). These elements focus an incident plane wave into a segment of the optical axis. The performances of the PDOEs are compared with those of multifocal lenses. In all cases, we obtained the point spread function and the image of an extended object. The results are presented and discussed. © 2015 SPIE.